Determining criterion of the operating temperature in the refractory brick entrained-flow gasifier based on the coal viscosity characteristics and slag flow process. (15th March 2022) - Lin, Kuo; Shen, Zhongjie; Liang, Qinfeng; Dai, Zhenghua; Xu, Jianliang; Guo, Xiaolei; Liu, Haifeng
Highlights: The heat transfer process in slag and refractory of the tapping hole was studied. The slag discharge behaviors based on viscosity characteristics were studied. The operating criterion for smooth slag discharge was proposed. Abstract: Entrained flow gasification technology is currently widely used in the coal chemical industry. However, the selection of candidate coal for achieving smooth slag discharge is significantly limited. Herein, the temperature distribution in the slag tapping hole of the refractory brick lining gasifier was analyzed. The effect of the slag viscosity-temperature characteristics on slag discharge behaviors was evaluated. Specific theoretical criteria rather than empirical estimation were proposed for selecting the operating temperature and candidate coal, which were important for industrial production. The results showed that the temperature in a localized area of the slag tapping hole was very low in current refractory-scheme, which induced the formation of solid-slag. The slag viscosity-temperature characteristics were found to be the key factors influencing the slag discharge process. Moreover, the operating parameters including the 'sensitive characteristic temperature' and 'no-solid slag characteristic temperature' were proposed, in which the temperature range was optimal for different slags.